2021
DOI: 10.1021/acsaelm.0c01127
|View full text |Cite
|
Sign up to set email alerts
|

Multiferroic h-LuFeO3 Thin Films on (111) and (100) Surfaces of YSZ Substrates: An Experimental and Theoretical Study

Abstract: Thin films of in-bulk unstable multiferroic hexagonal LuFeO 3 were synthesized on coherent (111) and for the first time on incoherent (100) YSZ and Pt/ YSZ surfaces by the metal−organic chemical vapor deposition (MOCVD) technique. The obtained films were thoroughly studied by X-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM), scanning electron microscopy (SEM), electron backscatter diffraction (EBSD), atomic force microscopy (AFM), piezoresponse force microscopy (PFM), and theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…19,20 In addition, according to molecular dynamics simulation of the interface between hexagonal LuFeO3 and YSZ (111), the Fe 3+ ions were considered to have been placed directly on the O 2ion of oxygen-terminated surface. 39 Analogous to their results, the prospective atomic structures of the interface between YSZ (111) and YbFe2O4 (0001) are illustrated in Figure 6. On the oxygen terminated YSZ (111) substrate, the Fe-O layer in YbFe2O4 was coherently matched to the topmost Zr-O layer.…”
Section: Resultssupporting
confidence: 65%
“…19,20 In addition, according to molecular dynamics simulation of the interface between hexagonal LuFeO3 and YSZ (111), the Fe 3+ ions were considered to have been placed directly on the O 2ion of oxygen-terminated surface. 39 Analogous to their results, the prospective atomic structures of the interface between YSZ (111) and YbFe2O4 (0001) are illustrated in Figure 6. On the oxygen terminated YSZ (111) substrate, the Fe-O layer in YbFe2O4 was coherently matched to the topmost Zr-O layer.…”
Section: Resultssupporting
confidence: 65%
“…It should be noted that epitaxial stabilization also changes the equilibrium characteristic phase relations between Fe 2 O 3 and LuFeO 3 : it is well known that in mixtures of powders of this and similar systems 6 a, c) indicate a higher uniformity and less surface roughness of the h-LuFeO 3 layer grown on YSZ(111) substrate compare to one deposited on YSZ(100). This observation can be explained by the previously described in-plane variant growth of h-LuFeO 3 on YSZ(100), which results in the formation of a films with microstructure fragmented into nanoscale domains [25]. The closer examination of images of heterostructure b-Fe 2 O 3 (001)//h-LuFeO 3 (001)//YSZ(100) revealed that h-LuFeO 3 had not formed located uniformly in one direction: its (001) planes were aligned parallel to both (001) and (111) planes of the YSZ substrate.…”
Section: Thin-film Heterostructures H-lufeo 3 +B-fe2omentioning
confidence: 66%
“…At the same time, in the heterostructure on the YSZ(100) substrate, b-Fe 2 O 3 grows in a different orientation relative to h-LuFeO 3 , which obviously leads to an increase in the critical thickness of this epitaxially stabilized layer. This interesting aspect, the dependence of the critical thickness on the orientetion of epitaxially stabilized phase, will be clarified by further calculations of the interface energies using the algorithm described by us in [25].…”
Section: Thin-film Heterostructures H-lufeo 3 +B-fe2omentioning
confidence: 99%
“…The lateral sides of the hexaferrite cores are free of magnetite, which indicates that the seeded growth of the spinel iron oxide occurs only on the spinel blocks of the hexaferrite structure, thus, the magnetite layers continue the hexaferrite structure. According to the results of HR-TEM with 2D FFT (Figure 2), HAADF STEM and SAED (Figure 3) the epitaxial relations between Fe3O4 and SrFe12O19 phases are following: The results of MD simulations based on the algorithm that was reported in [30], allowed us to propose the model of the interface that formed between Fe3O4 and SrFe12O19 phases (Figure 4). It should be noted that both SAED and simulation results yield the epitaxial relations that were stated above.…”
Section: Resultsmentioning
confidence: 94%